2011
DOI: 10.1021/cb100432x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Polyoxometalate Inhibitor of the DNA Binding Activity of Sox2

Abstract: Aberrant expression of transcription factors is a frequent cause of disease, yet drugs that modulate transcription factor protein-DNA interactions are presently unavailable. To this end, the chemical tractability of the DNA binding domain of the stem cell inducer and oncogene Sox2 was explored in a high-throughput fluorescence anisotropy screen. The screening revealed a Dawson polyoxometalate (K(6)[P(2)Mo(18)O(62)]) as a direct and nanomolar inhibitor of the DNA binding activity of Sox2. The Dawson polyoxometa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Some functionalized POMs have been used as inhibitors of HIV-1 protease 21 or the DNA-binding activity of Sox2 (ref. 22). Most recently, our group has reported that POMs can be excellent inhibitors to the aggregation of Ab, and, among them, the phosphotungstate with a Wells-Dawson structure (POM-Dawson) has the strongest inhibition effect 23 .…”
mentioning
confidence: 99%
“…Some functionalized POMs have been used as inhibitors of HIV-1 protease 21 or the DNA-binding activity of Sox2 (ref. 22). Most recently, our group has reported that POMs can be excellent inhibitors to the aggregation of Ab, and, among them, the phosphotungstate with a Wells-Dawson structure (POM-Dawson) has the strongest inhibition effect 23 .…”
mentioning
confidence: 99%
“…Hence addition of 2% DMSO alone acts as a negative control for the assay, as DMSO at 2% v/v does not influence the TF-DNA complex and hence the residual DNA binding activity measurements. Sox2-HMG domain was previously shown to be inhibited by the Dawson POM D1Mo (K 6 [P 2 Mo 18 O 62 ]) at an IC 50 of 98.6 ± 22.1 nM [7]. Using the IC 50 of Sox2 inhibition by the unmodified Dawson POM D1Mo (K 6 [P 2 Mo 18 O 62 ]) as a reference, all the different inhibitor compounds were added at a concentration of 125 nM to 15 different preassembled TF-DNA complexes.…”
Section: Methodsmentioning
confidence: 99%
“…However, those drugs do not bind the DNA binding domains (DBDs) of TFs because of their highly electrostatic nature, the lack of binding pockets, and the structural dynamics of TFs in the absence of DNA [6]. We hypothesized that the negatively charged Polyoxometalates (POMs) provide a suitable scaffold for targeting DBDs [7]. POMs are nanometer sized inorganic oxyanions comprising transition metals belonging to Group 5 and 6 of the periodic table in their highest oxidation states [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, polyoxometalates have long been studied in a variety of biological applications, from drug design to artificial enzymes , . Narasimhan et al identified polyoxometalate K 6 [P 2 Mo 18 O 62 ] to inhibit DNA‐bound Sox2 activity by spectroscopy (TROSY) experiments and molecular docking. Guan et al studied enzyme mimics (Ceria/POMs) with proteolytic and superoxide dismutase activities that are effective in degrading Ab aggregates and reducing intracellular reactive oxygen species (ROS) for the treatment of neurotoxicity of amyloid‐b peptide.…”
Section: Introductionmentioning
confidence: 99%